Phytochrome A Antagonizes PHYTOCHROME INTERACTING FACTOR 1 to Prevent Over-Activation of Photomorphogenesis - Krzymuski, Martin Javier (2014)
Phytochrome A (phyA) is crucial to initiate the early steps of the transition between skoto- and photomorphogenesis upon light exposure and to complete this process under far-red light (typical of dense vegetation canopies). However, under prolonged red or white light, phyA mutants are hyper-photomorphogenic in many respects. To investigate this issue, we analyzed the late response of the transcriptome of the phyA mutant to red light. Compared to the wildtype(WT), hyper-responsive genes outnumbered the genes showing reduced response to red light in phyA. A network analysis revealed the co-expression of PHYTOCHROME INTERACTING FACTOR 1 (PIF1) with those genes showing hyperpromotion by red light in phyA. The enhanced responses of gene expression, cotyledon unfolding, hypocotyl growth, and greening observed in the phyA mutant compared to the WT were absent in the phyA pif1 double mutant compared to pif1, indicating that the hyper-photomorphogenic phenotype of phyA requires PIF1. PIF1 directly binds to gene promoters that displayed PIF1-mediated enhanced response to red light. Expression of mutant PIF1 deficient in interactions with phyA and phyB enhanced the long-term growth response to red light but reduced the expression of selected genes in response to red light. We propose that phytochrome-mediated degradation of PIF1 prevents over-activation of photomorphogenesis during early seedling development.